Competitive Wrestling-related Injuries in School Aged Athletes in U.S. Emergency Departments - Myers, Richard J (Western Journal of Emergency Medicine, 2010)
Objective: To describe the characteristics of wrestling injuries occurring in male athletes aged 7-17 treated in United States (U.S.) emergency departments (ED) from 2000-2006, and to compare injury patterns between younger & older youth wrestlers.Methods: A stratified probability sample of U.S. hospitals providing emergency services in the National Electronic Injury Surveillance System was used for 2000-2006. ED visits for injuries sustained in organized wrestling were analyzed for male patients ages 7-17 years old (subdivided into 7-11 years old [youth group] and 12-17 years old [scholastic group]).Results: During the study period, there were an estimated 167,606 ED visits for wrestling injuries in 7-17 years old U.S. males, with 152,710 (91.1%) occurring in the older (12-17 years old) group. The annual injury incidence was 6.49 injuries/1,000 wrestlers in the youth group and 29.57 injuries/1,000 wrestlers in the scholastic group. The distribution of diagnoses was similar in both age groups, with sprain/strain as the most common diagnosis, followed by fracture and contusion/abrasion. Distributions of injury by location were significantly different between groups (p=0.02), although both groups exhibited approximately 75% of all injuries from the waist up. Overexertion and struck by/against were the most common precipitating and direct mechanisms in both groups, respectively. Over 97% of all injured wrestlers were treated and released.Conclusion: The types of injury in youth (7-11 years old) wrestlers are similar to those of scholastic (12-17 years old) wrestlers, although the distribution of body parts injured differs between the age groups. The majority of injuries occurs above the waist and may be a target for prevention strategies. [West J Emerg Med. 2010; 11(5):442-449.]